Pheromones from males of different familiarity exert divergent effects on adult neurogenesis in the female accessory olfactory bulb. Issue 8 (27th June 2013) - Wu, Jyun‐Han; Han, Yueh‐Ting; Yu, Jenn‐Yah; Wang, Tsu‐Wei
ABSTRACT Pheromones from urine of unfamiliar conspecific male animals can reinitiate a female's estrus cycle to cause pregnancy block through the vomeronasal organ (VNO)‐accessory olfactory bulb (AOB)‐hypothalamic pathway. This phenomenon is called the Bruce effect. Pheromones from the mate of the female, however, do not trigger re‐entrance of the estrus cycle because an olfactory memory toward its mate is formed. The activity of the VNO‐AOB‐hypothalamic pathway is negatively modulated by GABAergic granule cells in the AOB. Since these cells are constantly replenished by neural stem cells in the subventricular zone (SVZ) of the lateral ventricle throughout adulthood and adult neurogenesis is required for mate recognition and fertility, we tested the hypothesis that pheromones from familiar and unfamiliar males may have different effects on adult AOB neurogenesis in female mice. When female mice were exposed to bedding used by a male or lived with one, cell proliferation and neuroblast production in the SVZ were increased. Furthermore, survival of newly generated cells in the AOB was enhanced. This survival effect was transient and mediated by norepinephrine. Interestingly, male bedding‐induced newborn cell survival in the AOB but not cell proliferation in the SVZ was attenuated when females were subjected to bedding from an unfamiliar male. Our results indicate that male pheromones from familiar and unfamiliar males exert different effects on neurogenesis in the adult female AOB. Given that adult neurogenesis is required for reproductive behaviors, these divergent pheromonal effects may provide a mechanism for the Bruce effect. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 73: 632–645, 2013